Peran Wali Kelas dalam Bimbingan Konseling untuk Pembentukan Karakter Akhlakul Karimah Santriwati - Syarifah, Syarifah; Nurhasanah, Muwahidah; Sirojuddin, Akhmad; Paisun, Paisun; Wafa, Ali (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Expressions of joy, tremendous courage, and a high sense of self-worth all arise in the adolescent phase. As a result, children in this stage often make noisy and irritating noises. Adolescents in this stage have lofty, often unattainable goals and overly optimistic thinking. Their speech, which is often “normal,” becomes unpleasant or pathetic in this phase because they are very sensitive to the opinions of others. When viewed as children, especially young ones, they are highly resented. Based on this description, this research intends to examine how the role of homeroom teachers in guidance and counseling in the formation of the character of Akhlakul Karimah Santriwati Class 2 KMI (Kulliyatul Mu'allimat Al-Islamiyah) Pondok Modern Darussalam Gontor Putri Campus 1 Mantingan Ngawi. This research uses qualitative methods which include unstructured interviews, participant and non-participant observations, as well as documentation. From the research that took place at Pondok Modern Darussalam Gontor Putri campus 1, Mantingan, Ngawi, data processing revealed that homeroom teachers play an important role in the lives of grade 2 students because these students are undergoing a transition period that can lead to crisis. In boarding schools, homeroom teachers act as mentors and counselors, replacing the role of parents. In addition to being teachers and educators, homeroom teachers act as role models and motivators. Homeroom teachers play an important role in moral formation, mental growth, and positive personal development. In addition, homeroom teachers act as confidants and friends to their students, helping them overcome any problems. To improve the morale of their students, homeroom teachers should always provide assistance and counseling to their students before becoming friends and lovers and encouraging them to be more independent and more extreme in handling every problem they face.